2018
DOI: 10.1259/dmfr.20170084
|View full text |Cite
|
Sign up to set email alerts
|

Precision of cone beam CT to assess periodontal bone defects: a systematic review and meta-analysis

Abstract: Based on a moderate level of evidence, CBCT could be useful for furcation involvement periodontal cases, but it should only be used in cases where clinical evaluation and conventional radiographic imaging do not provide the information necessary for an adequate diagnosis and proper periodontal treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
0
26
0
3
Order By: Relevance
“…CBCT currently renders the only radiographic method to visualize the bony contour on the buccal and lingual surfaces [ 14 ]. A common way to measure alveolar bone level is to measure the distance from a reference landmark such as cemento-enamel junction (CEJ) to alveolar bone crest with or without comparing with the root length [ 16 , 17 ]. Leung et al scanned 334 teeth from human dry skulls by CBCT and found that, with a 0.38 mm reconstructed isotropic voxel, the CEJ and alveolar bone height could be measured with an accuracy of 0.4 mm and 0.6 mm respectively as compared with direct measurement by a digital caliper [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT currently renders the only radiographic method to visualize the bony contour on the buccal and lingual surfaces [ 14 ]. A common way to measure alveolar bone level is to measure the distance from a reference landmark such as cemento-enamel junction (CEJ) to alveolar bone crest with or without comparing with the root length [ 16 , 17 ]. Leung et al scanned 334 teeth from human dry skulls by CBCT and found that, with a 0.38 mm reconstructed isotropic voxel, the CEJ and alveolar bone height could be measured with an accuracy of 0.4 mm and 0.6 mm respectively as compared with direct measurement by a digital caliper [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining six studies [6,36,[96][97][98][99] were found to be systematic reviews for which the AMSTAR-2 assessment tool [100] was used. It is a popular instrument modified from the original AMSTAR, which contains 16 checklist questions.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Each review is supposed to adhere to the criteria provided by AMSTAR and scores YES whenever applicable. The review published by Haas et al [96] did not elaborate on whether they included the study registries or consulted content experts in the field in terms of comprehensive literature search strategy. Although a metaanalysis was conducted in such a review, the review authors did not assess the potential impact of risk of bias on the results of the meta-analysis or other evidence synthesis.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The remaining six studies [96] [99] were found to be a systematic review. The tool used for the critical appraisal and assessment of the systematic review was called AMSTAR2 [100] table5.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The review published by [96] did not elaborate on whether they included the study registries or consulted content experts in the field in terms of comprehensive literature search strategy. Although meta-analysis was conducted in such a review, the review authors did not assess the potential impact of risk of bias in individual studies on the results of the meta-analysis or other evidence synthesis.…”
Section: Systematic Reviewsmentioning
confidence: 99%